The impact of digital da'wah consumption intensity on anxiety levels in generation z students - Choirun Nisa; Mutiah Abdurrohman; Hilal Wahyu Gozali; Lucky Purwantini (Islamic perspective on Communication and Psychology, 2026)
Background: The development of digital technology has shifted the pattern of Islamic propagation (da'wah) from conventional to digital, utilizing platforms like YouTube, TikTok, and Instagram. Digital da'wah has now become the main medium for disseminating Islamic values, especially among Generation Z, who are known as digital natives with a high level of engagement with social media. This phenomenon raises questions regarding the influence of the intensity of watching digital da'wah content on psychological conditions, particularly anxiety, in university students. Based on the Uses and Gratifications theory and Spielberger's anxiety theory, this study aims to analyze the relationship between the intensity of watching digital da'wah and the anxiety levels of Generation Z students. Methods: The research employed a quantitative approach using a correlational method. The research subjects consisted of 60 students from Universitas Islam 45 Bekasi, selected using a convenience sampling technique. Data were collected through two psychological scales: the Digital Da'wah Watching Intensity Scale, developed based on Del Barrio's theory, and the Anxiety Scale, adapted from Spielberger's State-Trait Anxiety Inventory (STAI). Data analysis was performed using the Pearson correlation test, simple linear regression, and the Chi-Square test with SPSS. Findings: The results of the study indicated no significant relationship between the intensity of watching digital da'wah content and the students' anxiety levels (r =-0.135; p = 0.303), with a coefficient of determination (R^2) value of 0.018. This means that the intensity of watching only explains 1.8% of the variation in anxiety, while the remaining 98.2% is influenced by other factors such as academic pressure, social support, and personality. Descriptively, both variables were in the moderate category, indicating that although students actively watch digital da'wah content, it did not have a significant impact on reducing anxiety. The Chi-Square test results also indicated that some demographic factors, such as academic year, study program, activity, and the type of da'wah content, had a significant relationship with both watching intensity and anxiety levels. Conclusion: This study confirms that the effectiveness of digital da'wah is not determined by the frequency of viewing, but rather by the quality of the message and the delivery method that emphasizes empathy, compassion, and spiritual hope. Theoretically, this result reinforces the understanding that digital da'wah affects state anxiety (which is temporary), rather than established trait anxiety (which is fixed). Novelty/Originality of this article: This research is novel in examining the relationship between the intensity of watching digital da'wah and anxiety levels in Generation Z using a media psychology approach. The study highlights the phenomenon of micro-consumption of digital da'wah and finds that high frequency does not always correlate with a decrease in anxiety, thus offering a new perspective on the effectiveness of da'wah in the digital era.